Propagation Analysis for Automated Switching of Embedded RFID with GPS in Wireless Sensor Network Platform. (21st May 2015) - Poad, F. A.; Ismail, W.
Abstract : A 2.45 GHz active integrated ZigBee RFID system embedded with GPS is developed with an automated switching protocol algorithm utilizing wireless sensor network (WSN) platform to track the physical belongings or people in indoor and outdoor environments within a control area. In addition, to make the system contactless when the tag is not joining the network, the function of global system for mobile (GSM) communication is added to the integration. The communication between RFID reader and RFID tags is via WSN platform that supports mesh network and self-healing mechanism. Energy efficiency, robustness, and reliability are key factors in the design algorithm of the system. Comparisons are made between the existing active RFID system and the proposed active RFID system to study the performance of the proposed RFID system with an automated switching algorithm implemented on it. Based on the experimental study and statistical analysis done for all situations, a conclusion has been made where the proposed embedded RFID tag provided better signal propagation compared to the existing RFID tag and the battery lifetime for embedded RFID tag with switching mechanism is better than without switching mechanism.